Prototype Pendeteksi Beban Berlebih Untuk Keamanan Operasi Hydraulic Crane Di Kapal Penumpang - Ivana Wika Aprilia; Antonius Edy Kristiyono; Teguh Pribadi; Sonhaji Sonhaji; Wulan Marlia Sandi (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The safety and protection of the hydraulic crane is an important aspect that ensures the charging operation runs safely and efficiently, this study aims to provide protection against crane damage and minimize work accidents by providing overload detection sensors using loadcells and hx711 as the primary sensor in charging this device. This tool is a miniature crane that uses a servo motor and a DC motor as a replacement for the hydraulic on the crane. Where the same function, to move the arm of the crane and crane can rotate left, right, and up. The researchers used prototype methods to build and develop prototypes of cranes. To monitor this control system, use ESP32 as the transmitter and receiver of the joystick motion response. The received data will be processed and displayed on the LCD. Testing this device can detect how much load is lifted and detect if the load is over lifted, the device's operating system will lower the load again if overloaded.